The effect of nasal corticosteroid treatment on aerobic fitness in junior tennis player - Aziz, Lukman Hakim Abd (Universiti Sains Malaysia, 2016)
Objective of this study is to investigate the effect of nasal corticosteroid treatment on aerobic fitness in junior tennis players. Twenty junior tennis players aged 8-17 years old with average more than 1 year of tennis history background were recruited in this study. In the beginning of the study, standard multistage 20 m beep test run (pre-test) were carried out to determine the level of their aerobic fitness. After that, they were given a set of AQUA questionnaire to determine if they suffered from Allergic rhinitis (AR) or not. Accordingly, participants were grouped into AR and no AR groups. The AR group received nasal corticosteroid treatment (nasal spray) twice per day for 8 weeks. After 8 weeks, another standard multistage 20 m beep test run (posttest) were conducted. This study reveals that there were significant interaction between time (e.g ,. Pre- and post-tests) and treatment used (AR vs no AR) in this study. There were significant changes for AR group in terms of beep test level. The treatment of nasal spray were important for allergic rhinitis patient to maintain and increase the aerobic capacity thus to perform well.